Malaysia-Taiwan Relations and Taiwan’s New Southbound Policy - Yeoh, Emile Kok-Kheng; Lee, Chang; Yemo, Zhang (Malaysian Journal of International Relations, 2018)
The main objective of Taiwan’s New Southbound Policy is to reduce Taiwan’s economic dependence on Mainland China and seek a new engine for the economic development of Taiwan. Malaysia has the advantage of stable politics and open markets relative to other ASEAN countries. Under the “New Southbound Policy” launched in 2016 by Taiwan’s Tsai Ing-wen Administration to encourage local enterprises to invest in and trade with Southeast Asian countries. Malaysia as one of the most important Southeast Asian countries are attracting FDI from Taiwan with her rich natural resources, cheap labour cost, similar culture, and the easy-access sale network that connects ASEAN countries. Besides, other aspects including cultural and other societal, people-to-people, interactions also represent important foci of Taiwan-Malaysia bilateral relations under the New Southbound Policy.